A comparative fractional study to evaluate thermal performance of NaAlg–MoS2–Co hybrid nanofluid subject to shape factor and dual ramped conditions - Talha Anwar (Elsevier, 2022)
In the current century, hybrid nanofluids are considered one of the modified forms of heat transferring fluids because of their advanced thermal characteristics. The main motive of this article is the formulation of two different fractional models to explain flow patterns and thermal behavior of sodium alginate (NaAlg/SA) based hybrid nanofluid. The improvement in the thermal performance of NaAlg due to the addition of molybdenum-disulfide (MoS2) and cobalt (Co) nanoparticles is also analyzed. The ramped motion of an unbounded inclined plate leads to execute the flow of hybrid nanofluid through a porous material. The considered hybrid nanofluid also encounters magnetic effects. The heat transfer process starts due to the application of the ramped heating condition at the inclined boundary and thermal radiation, shape factor of nanoparticles, and heat injection/suction also affect this process. The mathematical modeling of the considered problem is carried out and two different fractional models are developed through Caputo-Fabrizio (CF) and Atangana-Baleanu (AB) fractional derivatives. Using the powerful Laplace transform technique, double mathematical and fractional analysis is performed to establish the analytic solutions. To clearly understand the heat transfer mechanism and behavior of shear stress, numerical simulations are performed for temperature and velocity gradients at the boundary. For a comprehensive physical investigation, several graphs and tables are furnished to evaluate the role of involved thermal and physical parameters in developing the flow patterns and temperature field. This study concludes that even dispersion of Co and MoS2 nanoparticles in NaAlg enhances the heat transfer rate of host fluid up to 21%. Comparative analysis suggests that AB fractional derivative is more adequate to describe the flow patterns and temperature field. Furthermore, maximum values of Nusselt number are observed when both nanoparticles are considered of blade shape.